Analisis Pengaruh ERP Dan Orientasi Pasar Terhadap Kinerja Pemasaran Melalui Keunggulan Bersaing Serta Pegaruh Lingkungan Industri Dan Orientasi Pasar Terhadap Kinerja Pemasaran Melalui Strategi Pemasaran (Studi Pada UMKM Di Kota Semarang) - Kurniawan, Erick Bagas; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2019)
This research was conducted to examine how much influence Enterprise ResourcePlanning (ERP), Market Orientation, Industry Environment, Competitive Advantage,Marketing Strategy to Marketing Performance. This study uses three independentvariables and also three dependent variable that consist of two variables have a role asintervening variableThe sample used in this study amounted to 207 MSMEs in Semarang City in 2019.Samples were taken using the Random Sampling method. The analysis used in this study isdata normality test, confirmatory test and hypothesis testing using the Structural EquationModeling (SEM) model.The results of this study indicate that ERP has a positive effect on competitiveadvantage significantly, market orientation has a positive effect on competitive advantage,market orientation has a positive effect on marketing strategies, industrial environment hasa positive effect on marketing strategies, competitive advantage has a positive effect onmarketing performance and influential marketing strategies positive for marketingperformance.